“Talking heads” in Portuguese sign and spoken languages - Marisa Cruz; Sónia Frota (Language and Cognition)
Head and eyebrow movements have been reported as question markers in both spoken (e.g. Swerts & Krahmer, 2004) and sign languages (e.g., Zeshan, 2004). However, the relative weight of these visual cues in conveying prosodic meaning remains unexplored. This study examines, through a kinematic analysis, if (and how) the amplitude of head falling movements varies in statements versus questions, both in Portuguese Sign Language (LGP) and in the spoken modality of European Portuguese. The results show that the head falling movement plays a key role in conveying interrogativity in Portuguese, in varying degrees. In LGP, the head amplitude is larger than in the spoken modality, and the shape of the head movement varies across sentence types, thus showing the primary role of this visual cue in LGP prosodic grammar. In spoken Portuguese, although the head amplitude also differs between sentence types, the shape of the movement over time is always the same (falling), thus pointing to a secondary/complementary role in spoken Portuguese.